Sovereign Debt Restructurings: Delays in Renegotiations and Risk Averse Creditors. Issue 5 (18th March 2020) - Asonuma, Tamon; Joo, Hyungseok
Abstract: Foreign creditors' business cycles influence both the process and the outcome of sovereign debt restructurings. We compile two datasets on creditor committees and chairs and on creditor business and financial cycles at the restructurings. We find that when creditors experience high GDP growth, restructurings are delayed and settled with smaller haircuts. To rationalize these stylized facts, we develop a theoretical model of sovereign debt with multiround renegotiations between a risk averse sovereign debtor and a risk averse creditor. The quantitative analysis of the model shows that high creditor income results in both longer delays in renegotiations and smaller haircuts. Our theoretical predictions are supported by data.